PENDAMPINGAN PEMANFAATAN PEKARANGAN RUMAH PERKOTAAN MELALUI BUDIDAYA PADI DALAM POLYBAG - Paiman, Paiman; Tri Kusumastuti, Cicilia; Ardiyanta, Ardiyanta (Universitas PGRI Yogyakarta, 2024)
The area of agricultural land around urban areas is getting smaller due to conversion to residential expansion which can no longer be controlled. Rice cultivation can also be done in polybags placed in the yard. The community service is entitled